À la recherche de savoirs perdus? Expérience, innovation et savoirs incorporés chez des agriculteurs biologiques au Québec - Mary Richardson (VertigO)
There has been relatively little research in the social sciences on knowledge generated and exchanged by farmers in modern Western contexts. Yet organic farmers in Quebec are at the heart of an intense innovation that is re-creating local knowledge on various elements of the living environment. They are reviving ancestral knowledge, developing new knowledge in light of scientific research, and constructing their own embodied forms of knowledge through practice, experimentation, observation, and trial and error, which they then share with other farmers, students and clients. This knowledge creation and sharing is part of a broader social change advocating a more ethical and ecological relation to nature (non-humans). The epistemological authority of science (in particular agronomy) is contested in favour of an ethical and holistic epistemology.